2008
DOI: 10.1186/1471-213x-8-102
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of human glial precursors

Abstract: Background: We have generated gene expression databases for human glial precursors, neuronal precursors, astrocyte precursors and neural stem cells and focused on comparing the profile of glial precursors with that of other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 53 publications
1
50
0
Order By: Relevance
“…9,11 The hGRP were differentiated into astrocytes by distinct protocols that were previously used to obtain astrocytes with different phenotypic properties including BMP-4 1,10,[15][16][17]19,42 and CNTF. 16,17,19,42 Cultures grown in the presence of bFGF were used to maintain the undifferentiated, immature state of glial progenitors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9,11 The hGRP were differentiated into astrocytes by distinct protocols that were previously used to obtain astrocytes with different phenotypic properties including BMP-4 1,10,[15][16][17]19,42 and CNTF. 16,17,19,42 Cultures grown in the presence of bFGF were used to maintain the undifferentiated, immature state of glial progenitors.…”
Section: Resultsmentioning
confidence: 99%
“…All protocols and procedures for hGRP isolation were reviewed by the Western Institutional Review Board (IRB), which deemed that any further IRB oversight was unnecessary. 9,11 Single-cell hGRP were purified by Miltenyi immunomagnetic columns as previously described. 9,11 Positively-selected cells were cultured for 20 days (two passages) in DMEM/F12 supplemented with 0.01% human serum albumin, penicillin/streptomycin/Fungizone, 1 · N2 supplement, 20 ng/mL basic fibroblast growth factor (bFGF), 10 ng/mL PDGF-AA, and 5 ng/mL NT-3.…”
Section: Preparation Of Hgrpmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we demonstrated that DACH1, a member of corepressor complexes, repressed FGF2 expression. Campanelli et al found the expression level of DACH1 in glial precursors was much higher than that in neural stem cells (NSCs) (33). Withdrawal of bFGF, which is known as a critical component of culture medium for human embryonic and neural stem cells (34), drives astrocytic differentiation (2,34,35).…”
Section: Dach1-spanning Region Is Indicated As a Target Of Copy Numbementioning
confidence: 99%